Penyuluhan Manfaat Gizi Daun Anggur untuk Meningkatkan Pemanfaatan Budidaya Lokal Masyarakat Desa Palur Kulon - Salwa Alifa Bestari; Ivanna Eka Putri Marisa; Karisma Larasati Adelia Prayogi; Putri Nayla Assyifa; Nabila Devita Rahmawati; Naufal Ramadhandi; Dita Andini Rahmawati; Vivi Dwi Nurhalizah; Umela Nuria Maris; Rhoma Dita Rizqa Aprilia; Aanisah Luthfiah Fawwaz; Widyadhari Yoanisa Saraswati; Zein Nur Azizah; Tazkia Aulia; Dinda Zhafira Mutya Kamila (Abdi Geomedisains, 2025)
The main problem faced by the community partners in Dusun Palur Kulon, Ngringo Village, is the limited knowledge of the health benefits of grape leaves, despite their existing cultivation in the area. As a result, grape leaves have not been optimally utilized as nutritious local food and lack health-based product branding. This community service program, conducted through a collaboration between lecturers and the Nutrition Student Association of Universitas Muhammadiyah Surakarta (UMS), aimed to improve community nutrition literacy through innovative utilization of grape leaves as healthy and value-added local food. The activity was carried out at the community’s request and consisted of an educational session, interactive discussions, a video demonstration on grape leaf chip processing, and a reflection session. A total of 37 community members participated actively. The materials covered nutritional value, health benefits, and proper processing techniques of grape leaves. The results indicated improved community understanding of the health benefits of grape leaves and increased interest in developing grape leaf–based food products. Evaluation through discussions and reflections showed that the interactive approach and audiovisual media were well received and easy to understand. Follow-up plans include continued assistance in product processing, strengthening health-based branding, and supporting the development of grape leaves as a sustainable local food product.